El contexto epistemológico de la pedagogía crítica en el ajuste curricular del Ecuador en el 2016 - Esteves, Zila Isabel (2019)
Like the other areas, in the curricular document, each areais structure in sub-levels, organizing thelearning in curricular blocks that respond own epistemological, didactic and pedagogical criteria. As epistemology brings knowledge from the object of knowledge, to the knowing subject, whichis usually the student, the way is knowledge is approached is the pedagogical, and the didactic the teacher intentionally brings that knowledge to the rest. From this point of view, a document is prepared to arrive at establishing the pedagogical and didactic parameters the are carryout in the curricular adjustment.Starting from each evaluation criterion, the essential and desirable learning that students have to achieve in each areais described, methodological orientations and examples of tasks are offered and the general objectives of the area to whose work is contributed are analyzed, analyzing some areas.